Power transformer failures: Sutf6-03 Case study at Uhe Samuel (Research, Society and Development, 2021)
Power transformers are among the most important pieces of equipment in the electrical system and are fundamental for the transmission and distribution of electrical energy, for which there is a need to be monitored and analyzed rigorously. Considering the importance of this equipment, this study sought to analyze the occurrence in the elevator transformer SUTF6-03 of the Samuel Hydroelectric Power Plant, which was removed from operation due to the performance of the differential protections. Based on the data generated due to the failure of the transformer, a case study was carried out to collect and analyze data from the reports sent by Eletronorte's Central Laboratory, of the transformer oil samples, where these data were compiled in the form of graphs. Research was done on the theory of transformers and fault diagnosis methods through oil analysis. This work shows that it is possible through the Rogers Method to diagnose the reason for the fault that occurred in the transformer.